2014
DOI: 10.1080/01446193.2014.938086
|View full text |Cite
|
Sign up to set email alerts
|

Economic development and construction productivity in Malaysia

Abstract: The productivity of the construction industry has a significant effect on national economic growth. Gains from higher construction productivity flow through the economy, as all industries rely on construction to some extent as part of their business investment. Contractions and expansions of economic activity are common phenomena in an economy. Three construction cycles occurred between the years 1970 and 2011 in Malaysia. The relationships between construction productivity and economic development are examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Completing projects in a predictable manner of time (within schedule) is one of the important indicators of project success. Cost overrun is one of the most frequent problems with construction projects and contractors are criticized for the common occurrence of cost overrun in construction projects, [36], [37]. There are some other factors which also contribute to the cost overrun such as profit of the project, project design cost, and wastage of materials, construction productivity, cost of variation orders and cost of rework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Completing projects in a predictable manner of time (within schedule) is one of the important indicators of project success. Cost overrun is one of the most frequent problems with construction projects and contractors are criticized for the common occurrence of cost overrun in construction projects, [36], [37]. There are some other factors which also contribute to the cost overrun such as profit of the project, project design cost, and wastage of materials, construction productivity, cost of variation orders and cost of rework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Country, data source, time frame Method/Design Findings Chia et al (2014), "Economic development and construction productivity in Malaysia"…”
Section: Sourcementioning
confidence: 99%
“…Since this sector influences the growth of national economy, its productivity level is of critical importance. Studies have proved that the higher the productiv-ity level of the construction sector, the higher the gains for other sectors, since the former feeds investments into the latter to some extent (Chia, Skitmore, Runeson, & Bridge, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of the construction sector with the economy has received attention from researchers worldwide. Numerous studies have examined and reported the relationship between construction sector output and the economy (Banaitienė, Banaitis, & Laučys, 2015;Chan, 2001;Giang & Low, 2011;Ma, Liu, & Reed, 2017;Ofori, 1990;Turin, 1978), while several others (Chia et al, 2014;Y. Gang, F. Gang, & Yan, 2003) have examined the relationship between this sector's productivity performance and economic development.…”
Section: Introductionmentioning
confidence: 99%